Advances in Econometrics Theory and Applications - Verbic, Miroslav (IntechOpen, 2011)
Econometrics is becoming a highly developed and highly mathematicized array of its own sub disciplines, as it should be, as economies are becoming increasingly complex, and scientific economic analyses require progressively thorough knowledge of solid quantitative methods. This book thus provides recent insight on some key issues in econometric theory and applications. The volume first focuses on three recent advances in econometric theory: non-parametric estimation, instrument generating functions, and seasonal volatility models. Additionally, three recent econometric applications are presented: continuous time duration analysis, panel data analysis dealing with endogeneity and selectivity biases, and seemingly unrelated regression analysis. Intended as an electronic edition, providing immediate "open access" to its content, the book is easy to follow and will be of interest to professionals involved in econometrics.